2020
DOI: 10.3390/ijms21218153
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Differentiated by Exosomes Isolated from Cancer Cells Promote Cancer Cell Invasion

Abstract: Cancer-associated fibroblasts (CAFs) in the cancer microenvironment play an essential role in metastasis. Differentiation of endothelial cells into CAFs is induced by cancer cell-derived exosomes secreted from cancer cells that transfer molecular signals to surrounding cells. Differentiated CAFs facilitate migration of cancer cells to different regions through promoting extracellular matrix (ECM) modifications. However, in vitro models in which endothelial cells exposed to cancer cell-derived exosomes secreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 63 publications
(68 reference statements)
1
10
0
Order By: Relevance
“…Exosomes can be released by CAFs and internalized by cancer cells or the other way around, as cancer cells can release exosomes to change normal fibroblasts (NFs) into CAFs. Cancer-derived exosomes can induce differentiation of endothelial cells to CAFs, of which the exosomes, in turn, can aid in cancer cell invasion [ 72 , 73 ]. Recent research identified CAF-secreted exosomes as playing a critical role in tumor–CAF crosstalk and in cancer cell invasion [ 70 ].…”
Section: Caf–tumor Communicationmentioning
confidence: 99%
“…Exosomes can be released by CAFs and internalized by cancer cells or the other way around, as cancer cells can release exosomes to change normal fibroblasts (NFs) into CAFs. Cancer-derived exosomes can induce differentiation of endothelial cells to CAFs, of which the exosomes, in turn, can aid in cancer cell invasion [ 72 , 73 ]. Recent research identified CAF-secreted exosomes as playing a critical role in tumor–CAF crosstalk and in cancer cell invasion [ 70 ].…”
Section: Caf–tumor Communicationmentioning
confidence: 99%
“…Exosomes from different types of cancer cells can efficiently induce EndoMT, in which endothelial cells undergo significant changes in phenotype, genotype and behavior. CAFs, in turn, gain the ability to remodel the ECM, to disrupt the vascular barrier and to stimulate the migration and invasion of cancer cells [ 150 ]. Conversely, mesenchymal stem cell-derived exosomes have the ability to reverse the EndoMT process via the recovery of CAFs back to endothelial cells [ 151 ].…”
Section: Exosome-mediated Remodeling Of Endothelial Gene Expressiomentioning
confidence: 99%
“…There is an enhancement in EMT and migration of cancer cells observed upon delivery of certain EV cargo such as CD81, ROCK2, FLOT1, and FAM129B, Galectin-1, and Sonic Hedgehog [ 34 , 35 , 36 ]. In fact, CAFs activated by cancer-derived EVs were observed to increase the invasive capacity of co-cultured cancer cells more than CAFs that were activated by cancer cells through direct interaction [ 37 ]. In addition, the core components of the planar cell polarity signaling pathway that controls tissue polarity have been shown to be essential for the EV-induced protrusive activity and motility of breast cancer cells [ 32 , 35 ].…”
Section: Fibroblastsmentioning
confidence: 99%